(untitled) (Malaysian Journal of Learning and Instruction, 2017)
Purpose â€“ The purpose of this study is to presents the steps taken to produce a mobile learning application framework to learn Microeconomics for which is named â€œMobiEko Appsâ€. Mobile learning application is utilized because the framework enables seamless access between all the involved actors. The design and development of an application prototype in this study are based on the ADDIE instructional design model. Methodology â€“ This study was conducted to develop an educational mobile application for Microeconomics by eliciting learning content and evaluating learnersâ€™ satisfaction after the use of app. The design and development of an application prototype in this study are based on the ADDIE instructional design model (Analysis, Design, Development, Implementation, and Evaluation). This approach provides educators with useful, clearly defined stages for the effective implementation of instruction. Five stages comprise the framework, each with its own distinct purpose and function in the progression of instructional design. In this study, Prototype applications that want to produce is an education material in the form of mobile application based on Android platform to support teaching and learning activities in the classroom. Findings â€“ A systematic research framework using ADDIE (Analyze, Design, Develop, Implement, and Evaluate) approach is proposed to produce mobile application (MobiEko app) by dividing the content of the application into four main activities namely as learning menu, learning activities, assessment activities and support activities. The findings also showed that students were satisfied of the presentation design, visual, navigation and accessibility of â€˜MobiEkoâ€™ application. Additionally, Mobile educational application (MobiEko) successfully performed as a knowledge transfer channel to help students and learners understand better the concepts and course contents as well as facilitated educators and students with better or more convenient ways in their teaching and learning activities. Significance â€“ The present study has great significance to explore the roles of self-directed learning through mobile application to enhance the studentâ€™s knowledge through the development of an educational mobile application. It is expected to encourage students to carry out self-study while improving the quality of teaching and learning activities in line with the 21st century learning. The education mobile application envisioned to be applied in blended learning scenario to support instructors and students in teaching and learning, leveraging on the affordance and ownership of mobile devices as well as to facilitate the learning of Microeconomics courses on mobile devices.